Relationship Between Noise-Related Risk Perception, Knowledge, and the Use of Hearing Protection Devices Among Para Rubber Wood Sawmill Workers - Phayong Thepaksorn; Wattasit Siriwong; Richard L. Neitzel; Ratana Somrongthong; Teeranee Techasrivichien (Elsevier, 2018)
Background: The understanding of the relationship between risk perception, knowledge, and protective behaviors could play a major role in occupational risk control and management. Research exploring how workers perceive, recognize, and react to risks in different occupational settings is scarce in Thailand. The aim of this study was to assess the relationship of noise-related risk perceptions and knowledge to the use of hearing protective devices (HPDs) among sawmill workers in Thailand. Methods: Sawmill workers (n = 540) from four factories in Trang, Southern Thailand, participated in a questionnaire interview from December 2015 to January 2016. Descriptive statistics and linear regression models were used to explore the risk factors related to HPD use. Path diagram analysis was demonstrated and used to evaluate associations. Results: Risk perception was significantly correlated with HPD use (p < 0.01), HPD training (p = 0.01), and the number of years of work experience (p = 0.03). Sawmill workers were likely to use HPDs based on their risk perception and HPD training. However, HPD training was inversely correlated with age and the number of years of work experience. Conclusion: The study highlights the importance of risk perceptions and knowledge, and these factors should be emphasized in the design and implementation of any personal safety intervention program for sawmill workers. Keywords: health hazards, hearing protective device, risk perceptions, sawmills